Prevalence of dyslipidemia among teachers in China: a systematic review and meta-analysis - Xiaoxue Wei; Xiaoxue Wei; Feng Ouyang; Yang Liu; Qingfeng Du; Qingfeng Du (Frontiers Media S.A., 2024)
ObjectiveTo systematically analyze the current situation with dyslipidemia among teachers in China, to provide guidance for lipid management and prevention of ASCVD.DesignA systematic review and meta-analysis of the prevalence of dyslipidemia among teachers in China.MethodsWe searched via 9 databases for studies published between June 1, 1996, and July, 25, 2024. The article were evaluated by the Joanna Briggs Institute (JBI) Article Quality Assessment Tool (2016) in Australia. RevMan5.0 and R4.3.1 software were used for statistical analysis to calculate the OR and RR values and the 95% confidence intervals. This systematic review and meta-analysis were reported in line with the PRISMA guidelines.ResultsA total of 12 cross-sectional studies from 10 provinces (regions) were included, with the sample of 24,851, including 12,626 males and 12,198 females, the average age of about 40 (1,036 were aged ≤30, 5,872 were aged 30-40, 3,854 were aged 40-50, 4,607 were aged 50-60, and 3,425 were aged ≥60), including 9,114 people with dyslipidemia. The overall prevalence of dyslipidemia among teachers in China was 38% (p < 0.01, 95% CI (1.27-1.95)). The prevalence of hypertriglyceridemia was 21.6% (p < 0.01, 95% CI (1.05-1.50)), that of hypercholesterolemia was 13.3% (p < 0.05, 95% CI (0.98-1.34)), that of hyper-LDL-Cemia was 9.4% (p < 0.01, 95% CI (1.04-1.59)), and that of hypo-HDL-Cemia was 4.3% (p = 0.25, 95% CI (0.61-6.52)). The heterogeneity of dyslipidemia among teachers of the different sexes was I2 = 92% (p < 0.01). The overall prevalence of dyslipidemia, as well as that of high TC, high TG, and high LDL-C levels, was greater in female teachers than in male teachers (df = 10, 95% CI:1.35-1.52, p < 0.01). The heterogeneity of dyslipidemia among teachers of different ages was I2 = 74% (p < 0.01), and the risk was lower for aged <50 years than those aged ≥50 years (df = 7, 95% CI: 0.38-0.44, p = 0.04). The year, region, school type, and these factors showed no effect on the prevalence of dyslipidemia (p = 0.7353).ConclusionThe prevalence of dyslipidemia in the teacher population in China is high and tends to increase with age. We should pay attention to the health management of the teachers, which can be done by appropriately adjusting the educational model settings, increasing the programs on physical activities, promoting the improvement of healthy lifestyles.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier [CRD42024567785].